Efektivitas Buku Aku Senang Belajar Membaca Berbasis Montessori untuk Anak Usia Dini: Kajian Literatur Sistematik - Nurhalita Diny; Erie Siti Syarah (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study evaluates the effectiveness of the “Aku Senang Belajar Membaca” book, de signed based on the Montessori method, for early childhood learners aged 3–7 years. Em ploying a Systematic Literature Review (SLR), this research synthesizes findings from literature published between 2015 and 2025. The book, structured in four levels with culturally relevant Indonesian vocabulary and supported by Montessori materials like sandpaper letters, fosters reading interest, letter recognition, and confidence in early reading. Results indicate that integrating the book with Montessori media enhances phonological awareness, motivation, and engagement in literacy activities. These find ings underscore the importance of contextual and concrete learning materials for early childhood education, offering insights for educators and curriculum developers to improve literacy interventions in Indonesia.